Water! : why every drop counts and how you can start making waves to protect it - Gerry, Lisa (Washington, DC : National Geographic Kids, 2023)
"Water supports all life on Earth, but it's disappearing fast. How do we fight for it? It's time to take a close look at water-what we have available, how to conserve it, how to distribute it, and how to manage it for future generations to come. Next up in this core National Geographic, mission-oriented series, which includes the award-winning This Book Stinks and Kids vs Plastic, this book will be loaded with super wow-worthy water stats, infographics, and weird but true information and focus on everything about water"--
Ages 8-12
Grades 4-6
Keywords: Water -- Juvenile literature